PENGARUH MODAL, TEKNOLOGI, DAN TENAGA KERJA TERHADAP PENDAPATAN PENGRAJIN KAIN ENDEK DI KABUPATEN KLUNGKUNG - Pratiwi, Komang Winda; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.06.TAHUN.2024DO - 10.24843/EEB.2024.v13.i06.p20, 2024)
The industrial sector is a sector that has a very important role in the economy. One of the well-developed industries in Bali is the endek fabric industry . Klungkung Regency is one of the regencies with the highest number of processing industries in Bali Province, one of which is the endek fabric industry. This study aims to determine the effect of capital, technology , and labor on the income of the endek fabric industry in Klungkung Regency. The data used in this study is primary data, which is by conducting non-participant observations and structured interviews using a list of questions that have been provided. The population used in this study were all endek fabric craftsmen in Klungkung Regency with the number of samples used as many as 96 respondents using saturated sampling technique. The analysis technique used in this research is multiple linear regression. The results of the study stated that the variables of capital, technology , and labor simultaneously had a significant effect on the income of endek fabric craftsmen in Klungkung Regency and the variables of capital, technology , and labor partially had a positive effect on the income of endek fabric craftsmen in Klungkung Regency.